Formulation And Physical Stability Test Of Facial Wash Gel Ethanol Extract Of White Frangipani Plumeria Alba Flower (Plumeria Alba) With Hidroxy Propyl Methyl Cellulose (Hpmc) As Gelling Agent: FORMULATION AND PHYSICAL STABILITY TEST OF FACIAL WASH GEL ETHANOL EXTRACT OF WHITE FRANGIPANI PLUMERIA ALBA FLOWER (Plumeria alba) WITH Hidroxy Propyl Methyl Cellulose (HPMC) AS GELLING AGENT - Amirah, Hilda Amirah (JURNAL FARMASI GALENIKA, 2023)
White Cambodian flower (Plumeria alba) contains secondary metabolite compounds in the form of flavonoids, tannins, alkaloids, and saponins. The purpose of this study was to determine whether the 96% ethanol extract of the white frangipani flower (Plueria lba) could be formulated into a facial wash gel preparation formulated with HPMC base in terms of stability. White frangipani flowers were extracted by maceration method with 96% ethanol solvent ratio 1:4. The facial wash gel of white frangipani flower extract was made into 4 formulations with different concentrations, namely 0%, 1%, 2%, and 2.5%. The facial wash gel formulation was then evaluated for its physical stability using the Freez thaw cycling method and hedonic and irritation tests were carried out on 10 respondents. The results showed that differences in the concentration of white frangipani flower extract could affect physical stability, respondents' interest and irritation. Good physical stability test results are found in the F1 and F2 formulations where the pH, foam height, organoleptic and homogeneity tests have met the requirements for facial wash gel preparations but in the dispersion test they do not meet the requirements. while for the interest of respondents, a good formulation is the F2 formulation.